Membaca Ideologi Kaum Revivalis Islam dalam Perspektif Jender - Syafii, Syafii (Musawa Jurnal Studi Gender dan Islam, 2010)
Women, as individuals and as an issue, are often neglected in the agendas of Islamic revivalist movements. Their main priority is the reinstatement of previous Islamic glory and power, a return to the golden age of Islam, primarily to the years of and shortly fallowing the prophet. Revivalist ideologies differ depending on the nation and culture of origin. Those currently prevalent in Indonesia tend to be on the transnationalist path. That is that they dream of an Islamic Nation-State, one run under the banner of Khilafah, the so perceived ideal Islamic government. They seem to have forgotten the Prophet's fight for gender equality. The issue being drowned out by other, less gender concerning issues hotly advocated. Thus many of their followers are decidedly blind towards on holistic Islamic Spirituality, especially those on women and gender, two issues in need of more intense notice.